Amount of nutrients in stalk of sugar cane as a function of sources and doses of manganese - Benett, Cleiton Gredson Sabin; Buzetti, Salatier; Silva, Katiane Santiago; Teixeira Filho, Marcelo Carvalho Minhoto; Costa, Nídia Raquel; Maeda, Alexandra Sanae; Andreotti, Marcelo (Semina: Ciências Agrárias, 2013)
The low productivity of sugarcane crop in some areas can be correlated with the lack of nutrients due to cane sugar crop be a major exporter of nutrients. The objective this study was to evaluate the effect of five doses and three sources of manganese applied in the planting furrow in sugar cane plant and its residual effects on ratoon cane, in the northwest region of São Paulo. The experiment was conducted at the site Fujimoto, area administered by the Valley Distillery Parana S/A Sugar and Alcohol in Suzanápolis - SP. The experimental design was randomized blocks in a factorial scheme 5x3, with five doses of manganese (0, 2.5, 5.0, 7.5 and 10.0 kg ha-1) and three sources (sulfate, chelate and FTE), applied at planting furrow in 4 repetitions. The plots consisted of four rows 5 m long, spaced by 1.5 m. The variety used was RB 86-7515. We assessed the accumulation of macro and micronutrients in stems, dry matter yield of stalks and stems. The sources and doses of manganese influenced the accumulation of macro and micronutrients and the dry stalks of sugar cane plant and ratoon cane. The stalk productivity was not affected by doses and sources of manganese in any crops.